Analisis Nilai Tambah Produk Kertas Kemasan Pangan Anti Mikroba Berbahan Baku Kulit Biji Kakao - Anugrah Hidayat; Azhar Bafadal; Tamrin Tamrin (Universitas Halu Oleo, 2021)
The purpose of this study was to analyze the value added of anti-microbial food packaging paper products made from cocoa bean shells. The study was conducted at the CV. Sultan of Agro-Maritime Industry Kendari City, Southeast Sulawesi Province. The location of this research was determined purposively. The study was conducted in July 2019 - July 2020. Types and sources of data include primary data obtained through interviews with respondents in the cocoa processing industry (Kalla Kakao Industri and CV. Sultan Agro-Maritime Industri) and relevant secondary data. Data collection techniques are carried out by in-depth interviews with key respondents or main respondents, and literature studies. The data analysis used in this study is the analysis of value added using the Hayami method. The results showed that the value added of cocoa bean shell waste into antimicrobial food packaging paper products was IDR 34,313 / kg.Keywords: cocoa bean shells; packaging paper; value-added